In vitro Evaluation of Copper Tolerance and Accumulation in Populus nigra - Vuksanović, Vanja; Kovačević, Branislav; Katanić, Marina; Orlović, Saša; Miladinović, Dragana (Archives of Biological Sciences, 2017)
Phytoextraction is an efficient and cheap way to extract copper from soils in riparian zones. In this work five genotypes of the endangered tree species Populus nigra L. were tested for their copper tolerance and accumulation in vitro when cultivated on media with three Cu concentrations: 10-3, 10-4 and 10-7 M (buffered with citric acid/Na-citrate buffer, pH 3 before sterilization). After five-weeks cultivation of rooted shoots, the highest increases in morphological and biomass parameters were observed at 10-7 M Cu2+. As the medium with 10-3 M Cu2+ exhibited a toxic effect, the effect of 10-4 M Cu2+ and pH 3 was used for further genotype evaluation. According to the measured morphological and parameters of photosynthetic pigment contents, the best performance was achieved by the genotype Populus nigra cl. DN3. The highest copper accumulation on the same medium was achieved by genotype Populus nigra cl. BN5. The obtained data point to the considerable potential of the applied method in the evaluation of Populus nigra genotypes for use in projects of copper phytoextraction. https://doi.org/10.2298/ABS170210014V Received: February 10, 2017; Revised: April 6, 2017; Accepted: April 26, 2017; Published online: May 15, 2017 How to cite this article: Vuksanović V, Kovačević B, Katanić M, Orlović S, Miladinović D. In vitro evaluation of copper tolerance and accumulation in Populus nigra. Arch Biol Sci. 2017;69(4):679-87.